Design and Strength Analysis of an Amphibious Multipurpose Dredger for the Eastern Surabaya Shipping Lane and the Porong River in Sidoarjo - Herijono, Boedi; Wijayanto, Fangki Indra; Putra, Muhammad Ryski Syah; Nugroho, Priyambodo Nur Ardi (International Journal of Marine Engineering Innovation and Research, 2025)
This study investigates the problem of sedimentation in the Porong River and the Eastern Surabaya Shipping Lane by taking a close look at the Amphibious Multipurpose Dredger. The study examines the vessel's parameters (length: 14.30 m, breadth: 4.70 m, height: 1.60 m, draft: 1.10 m) in light of the requirements of coastal reclamation. For stability and pressure studies, manual calculations and Finite Element Method simulations are utilised. The results show that the hollow Spud design is superior to the alternatives in terms of material efficiency (Safety Factor: 12.4032). The research makes a substantial contribution by offering an effective way to address sedimentation issues through improved dredger design. Moreover, it emphasizes the crucial part that an adaptable amphibious multipurpose dredger plays in reducing sedimentation. The study highlights the strategic significance of the recommended spud design, satisfying safety regulations and improving operational efficiency, as coastal ecosystems face rising challenges. For practitioners in environmental and maritime engineering looking for sustainable approaches to the development of coastal infrastructure, this paper is an invaluable resource.